Crossing Comb Ridge: Pottery Production and Procurement Among Southeast Utah Great House Communities. Issue 3 (July 2015) - Glowacki, Donna M.; Ferguson, Jeffrey R.; Hurst, Winston; Cameron, Catherine M.
Abstract : Understanding how the Chaco regional system operated requires examining the social networks maintained by great house communities during both the peak and decline ofChaco's influence. We used neutron activation analysis (NAA) of pottery, kiln wasters, and clays from three great house communities in southeast Utah (Bluff, Cottonwood Wash, and Comb Wash) to examine pottery production and the interaction networks of their residents. West of Comb Ridge, most gray ware jars or the materials they were made from were imported from east of Comb Ridge in both Chaco and post-Chaco times, while importation of painted white wares changed in the post-Chaco era as local production increased. This counters the expectation that painted pots are more likely to be exchanged than cooking jars. Kiln sherds and prepared clays are shown to be better identifiers of production area than raw clays, and paste color is confirmed as a useful clay source indicator in the Comb Ridge vicinity. Great house communities in the Comb Ridge area continued to exchange pots and/or ceramic raw materials in the post-Chaco era, but there is evidence for shifting social networks and intensified local production of white ware.